Episodic homelessness and health care utilization in a prospective cohort of HIV-infected persons with alcohol problems - Horton Nicholas J; Tibbetts Nicole; Kertesz Stefan G; Kim Theresa W; Samet Jeffrey H (BMC, 2006)
Abstract Background Because individuals with HIV/AIDS often have complex medical and social needs, the impact of housing status on medical service utilization is difficult to isolate from the impact of conditions that may worsen during periods of homelessness such as depression and substance abuse. We examine whether episodes of homelessness are independently associated with suboptimal medical utilization even when accounting for concurrent addiction severity and depression. Methods We used data from a 30-month cohort of patients with HIV/AIDS and alcohol problems. Housing status, utilization (ambulatory visits, emergency department (ED) visits, and hospitalizations) and other features were assessed with standardized research interviews at 6-month intervals. Multivariable longitudinal regression models calculated incidence rate ratios (IRR) comparing utilization rates during 6-month intervals (homeless versus housed). Additional models assessed whether addiction severity and depressive symptoms could account for utilization differences. Results Of the 349 subjects, 139 (39%) reported homelessness at least once during the study period; among these subjects, the median number of nights homeless per 6-month interview period was 30. Homelessness was associated with higher ED utilization (IRR = 2.17; 95% CI = 1.72-2.74) and hospitalizations (IRR = 2.30; 1.70-3.12), despite no difference in ambulatory care utilization (IRR = 1.09; 0.89-1.33). These associations were attenuated but remained significant when adjusting for addiction severity and depressive symptoms. Conclusion In patients with HIV/AIDS and alcohol problems, efforts to improve housing stability may help to mitigate intensive medical utilization patterns.